The Function of the Waltz in Valses y otras falsas confesiones (1972) by Blanca Varela - Fernández Cozman, Camilo Rubén (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The Creole waltz is a musical genre practiced in Peru since the end of the 19th century. It has an important function in Valses y otras falsas confesiones (1972) by the Peruvian poet Blanca Varela, a member of the “Generation of ‘50”. Some representative poems of Valses y otras falsas confesiones [Waltzes and other false confessions] are analyzed through the concept of demystification (proposed by Umberto Eco) and the theoretical framework of Stefano Arduini’s General Textual Rhetoric. Our central purpose is to state that, for Varela, there are two types of waltz: the criollo and the one that defends marginal groups. Varela demystifies the Creole waltz and, at the same time, formulates another type of waltz that takes the side of peripheral groups.